(untitled) (Conferencea, 2023)
For a long time, the issue of educational motivation does not cease to interest psychologists, teachers, and methodologists. This problem is of particular importance now. Education in higher education is considered as a process of forming a student’s personality, capable of self-development, self-improvement, and creative realization. Achievement of the designated goal is possible only under the condition of the development of the student’s creative activity, the formation of a motivational basis for training.